Investigating spatiotemporal and kinematic gait parameters in individuals with Parkinson’s disease with a history of freezing of gait and exploring the effects of dopaminergic therapy on freezing of gait subtypes - Lin, Po-Hsi; Lai, Yun-Ru; Lien, Chia-Yi; Huang, Chih-Cheng; Chiang, Yi-Fang; Kung, Chien-Feng; Chen, Chih-Jui; Lu, Cheng-Hsien (Frontiers in Neuroscience, 2024)
Introduction: Freezing of Gait (FOG) is a prevalent and debilitating symptom in idiopathic Parkinson’s disease (PD). This study evaluated spatiotemporal and kinematic gait parameters in individuals with PD with a history of FOG and explored the effects of dopaminergic therapy on FOG subtypes Methods: One hundred and nine individuals with PD underwent clinical assessments and quantitative biomechanical measures during walking cycles before and after dopaminergic therapy. Individuals with FOG were classified into levodopa-responsive and levodopa-unresponsive groups. Results: Individuals with FOG displayed longer disease duration and higher Unified Parkinson's Disease Rating Scale (UPDRS) II, III, IV scores, and total scores and levodopa equivalent dose, than those without FOG (all p<0.0001). Following propensity score matching of 15 pairs based on UPDRS total score and disease duration during the off-medication state, the analysis comparing the FOG and non-FOG groups revealed no significant differences in spatiotemporal and kinematic parameters. In 39 cases of FOG, dopaminergic therapy improved gait performance in individuals with PD, enhancing spatiotemporal parameters (speed, stride length, step length, step variability) and kinematic parameters (shoulder and elbow flexion/extension range of motion (ROM), pelvic rotation, and hip abduction/adduction ROM) regardless of FOG responsiveness to dopaminergic therapy. A significant difference in trunk sway ROM (p=0.029) remained before and after dopaminergic therapy, even after adjusting for disease duration and clinical severity. Discussion: Dopaminergic therapy had varying effects on PD with FOG, improving several spatiotemporal and kinematic gait parameters but being less effective in levodopa-unresponsive cases. Quantitative biomechanical measures offer detailed insights into gait performance, aiding personalized fall risk assessment and guiding individualized rehabilitation programs.